Preoperative Platelet Count Correlates With Postoperative Perineural Invasion on Specimen in Patients Treated With Radical Prostatectomy - Wang, Fangming; Liu, Fei; Liang, Jing; Yang, Feiya; Xing, Nianzeng (Frontiers in Oncology, 2022)
Objective: It has been reported that perineural invasion (PNI) after radical prostatectomy (RP) is associated with unfavorable prostate cancer (PCa) prognosis. However, the clinicopathological factors especially hematological parameters that influenced PNI remains unknown. Our aim was to explore the relationship between clinicopathological parameters and PNI in patients who underwent RP. Methods: A total of 348 PCa patients who underwent RP at our center between 2018 and 2021 were consecutively collected. We divided them into non-PNI and PNI groups based on PNI status, and compared clinicopathological characteristics including hematological parameters between non-PNI and PNI groups. The association of clinicopathological parameters including whole blood parameters, age, body mass index (BMI), hypertension, diabetes mellitus, prostate-specific antigen (PSA), ISUP (international society of urological pathology) grade, pathological stage T (pT), and neoadjuvant hormonal therapy (NHT) with PNI was determined by univariate and multivariate logistic regression analyses. Results: The pathological results of the RP specimen consisted of 254 (73.0%) patients with PNI and 94 (27.0%) cases without PNI. The level of PSA, percentages of advanced pT and grade, positive surgical margin rate, and vessel carcinoma embolus rate were significantly higher in the PNI group when compared with non-PNI counterpart (p=0.007, p<0.001, p<0.001, p<0.001, p<0.001, respectively). Among the whole blood parameters, only platelet count and plateletcrit were significantly different [216 (178.8-252.0) vs. 200.5 (173.5-236.5), p=0.04; 0.0021 (0.0018-0.0025) vs. 0.0020 (0.0017-0.0023), p=0.008, respectively]. Univariate logistic regression analysis demonstrated that platelet, ISUP, and pT were all positively correlated with the presence of PNI (T3 vs. T1, OR = 2.029, p=0.020; OR = 1.697, p<0.001; OR=3.836, p<0.001). In the stepwise multivariate regression analysis, the association between platelet and PNI remained significant (T2 vs. T1, OR = 2.171, 95% CI: 1.082-4.354, p = 0.029; T3 vs. T1, OR = 2.595, 95% CI: 1.259-5.349, p = 0.010) after adjusting for confounding factors including age, BMI, hypertension, diabetes mellitus, PSA, ISUP, pT, and NHT. Conclusions: The study first revealed that platelet count rather than other whole blood parameters was independently associated with the presence of PNI in PCa patients, suggesting that platelet might play an essential role in PCa aggressiveness.